2005
DOI: 10.1017/s0317167100003991
|View full text |Cite
|
Sign up to set email alerts
|

Inspiratory Muscle Training and the Perception of Dyspnea in Parkinson's Disease

Abstract: ABSTRACT:Background:Pulmonary and respiratory muscle function impairment are common in patients with Parkinson's disease (PD). Inspiratory muscle training may improve strength, dyspnea and functional capacity in healthy subjects and in those with chronic obstructive pulmonary disease. This study investigated the effect of specific inspiratory muscle training (SIMT) on pulmonary functions, inspiratory muscle performance, dyspnea and quality of life, in patients with PD.Patients and Methods:Twenty patients with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
95
1
4

Year Published

2007
2007
2017
2017

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 74 publications
(101 citation statements)
references
References 29 publications
(19 reference statements)
1
95
1
4
Order By: Relevance
“…The reduced Pod reported is not consistent with a more recent study, 23 which showed Pd patients to have a heightened Pod that decreased signifi cantly after levodopa administration, yet still remained higher than normal subjects. The patients studied may explain this increased Pod reported, as in contrast to the fi rst paper, 19 they had longstanding Pd and had abnormal pulmonary function tests.…”
Section: Abnormal Central Control Of Ventilationcontrasting
confidence: 99%
“…The reduced Pod reported is not consistent with a more recent study, 23 which showed Pd patients to have a heightened Pod that decreased signifi cantly after levodopa administration, yet still remained higher than normal subjects. The patients studied may explain this increased Pod reported, as in contrast to the fi rst paper, 19 they had longstanding Pd and had abnormal pulmonary function tests.…”
Section: Abnormal Central Control Of Ventilationcontrasting
confidence: 99%
“…[33]. Пациенты были распределены в группу срав-нения (ложная дыхательная гимнастика) и основную (ды-хательная гимнастика).…”
Section: методы лфк и эрготерапии в лечении бпunclassified
“…This is a valuable small effective device that can easily be used in clinics, hospitals or even at home operated by the patient. There is published evidence regarding the improvement of respiratory function, respiratory muscle strength, exercise capacity, quality of life and functional capacity in patients with Multiple Sclerosis (35,36) , Parkinson's disease (37), and Myasthenia Gravis (38) after having follow a program of inspiratory muscle training (IMT) with threshold load. These results suggest that IMT may be beneficial for individuals with neurological diseases.…”
Section: Treino Muscular Respiratóriomentioning
confidence: 99%
“…Trata-se de um dispositivo vantajoso, pequeno, eficaz e que pode ser utilizado com facilidade em clínicas, hospitais ou até mesmo em casa pelo próprio paciente. Na literatura científica já existem evidências sobre a melhora da função respiratória, da força dos músculos respiratórios, capacidade de exercício, qualidade de vida e capacidade funcional em pacientes com Esclerose Múltipla (35,36) ; Doença de Parkinson (37) e Miastenia Gravis (38) submetidos ao um programa de treino muscular inspiratório com carga limiar. Tais resultados sugerem que esse tipo de treino pode ser benéfico em indivíduos com doenças neurológicas.…”
Section: Treino Muscular Respiratóriounclassified